Total synthesis of TMG-chitotriomycin based on an automated electrochemical assembly of a disaccharide building block - Isoda, Yuta; Sasaki, Norihiko; Kitamura, Kei; Takahashi, Shuji; Manmode, Sujit; Takeda-Okuda, Naoko; Tamura, Jun-ichi; Nokami, Toshiki; Itoh, Toshiyuki (Beilstein Journal of Organic Chemistry, 2017)
The total synthesis of TMG-chitotriomycin using an automated electrochemical synthesizer for the assembly of carbohydrate building blocks is demonstrated. We have successfully prepared a precursor of TMG-chitotriomycin, which is a structurally-pure tetrasaccharide with typical protecting groups, through the methodology of automated electrochemical solution-phase synthesis developed by us. The synthesis of structurally well-defined TMG-chitotriomycin has been accomplished in 10-steps from a disaccharide building block.
Keywords: automated synthesis; electrochemical oxidation; glycosylation; glucosamine; total synthesis